Obesity in the elderly - Penny Montenegro, Eduardo (2017)
Older people are not exempt of being overweight or obese; in Peru this occurs respectively in 21.4% and 11.9% of the elderly, less than in people of younger age. Overweight and obesity are associated to noncommunicable chronic diseases, and to increase in morbidity and mortality. There is no trustworthy data on the optimum body-mass index in the elderly, but we use both the body-mass index and measurement of the abdominal circumference. Best efforts should be done to prevent this problem before subjects become seniors. Management should be gradual and safe, consisting mainly in behavioral interventions (adequate nutrition and physical activities) and drugs only when necessary.